A study on patients with alcohol dependence syndrome on tablet baclofen in a tertiary care hospital - N., Harshitha; M., Rakshitha; Kumar K., Pawan; Edagotu, Sukanya; Pandiyan, Kasthuri (International Journal of Research in Medical Sciences, 2024)
Background: Many clinical trials indicate that baclofen, a gamma-aminobutyric acid agonist has efficacy for alcohol dependence to reduce the cravings of alcohol and it may also have certain common or rare ADRs. Aim was to evaluate tablet baclofen’s adverse effects and sociodemographic profile in the treatment of ADS. Methods: This study was carried out in MVJ Medical College and Research Hospital Bangalore, India. The socio-demographic questionnaire and NADRP was administered to 100 patients who was on tablet baclofen with alcohol dependence syndrome that were diagnosed according to the ICD-10 diagnostic criteria, as well as 100 subject all of whom gave their informed consent. The data were analysed using Microsoft excel. Results: As a result, this present data analysis revealing that alcohol addiction was more prevalent in the 36 to 50 age group, men among women. Primary school students were more addicted to alcohol, with non-professionals, rural areas, and nuclear families having higher addiction rates. Most alcohol dependence subjects have a tobacco history and comorbid mental and behavioral disorders. NADRP scales indicate no severe adverse drug reactions in alcohol dependence syndrome patients. Conclusions: Results showed that ADS is more prevalent in the adults, married patients lack of education, occupation, and family size also contributed to addiction. Rural areas had higher alcohol addictions than urban ones, and nuclear families were more likely to abuse drugs. The study concluded that tab. baclofen is a rational medicine for treating ADS.